ZECA VACCARIANO: RISE TO POWER THROUGH SOCIAL BANDITRY IN SOUTHERN BRAZIL DURING THE FIRST REPUBLIC - Matielo, Ernoi Luiz; da Rocha, Humberto José (Seven Editora, 2026)
This article addresses the trajectory of José Antonio de Oliveira, known as Zeca Vaccariano, who carried out the assault on the group of payers on the São Paulo-Rio Grande Railroad, which took place on October 24, 1909, in the interior of the state of Santa Catarina, in southern Brazil. Theoretically, the work is guided by the perspective of social banditry, against the background of the historical context of the old republic in which a modernization process is articulated in the region under the aegis of mandonism. This is developed methodologically supported by bibliographical and documental research. As a central objective, the text discusses how social banditry represents an element inherent to the social dynamics of that space-time, providing the protagonist with an ascent from robber to police chief.